Developing Maqashid-Based Mosque Empowerment Index : A Case Study - Aisyah As-Salafiyah (SMART Insight, 2022)
This study aims to formulate a Maqashid Syariah-based mosque empowerment index formula as a measuring tool for the level of mosque empowerment. The data analysis technique uses the Analytical Network Process (ANP) with Super Decision 2.10 software to construct the index model structure. The results of this study produce an index of mosque empowerment which is composed of 6 criteria, namely elements of Maqashid Syariah; protecting religion, soul, intellect, lineage, wealth and environment. The results of the weighting of the criteria indicate that maintaining religion is the main criterion with a weighted value of 0.209. Each of these criteria consists of 5 indicators. Of all indicators, environmental safety is the top priority with a weighted value of 0.056. The results of the calculation of the formula in the three model mosques showed different results. The Andalusia Mosque occupies the top position with a value of 0.96 which is categorized as a very empowered mosque. Then the Ar-Rahman mosque with a value of 0.69 which is categorized as an empowered mosque. Finally, the Al-Muhaajirin mosque with a value of 0.57 so that is included in the category of the mosque that is quite empowered and can be prioritized for assistance.